Dinamika Wacana Keagamaan dalam Situasi Krisis: Antara Konservatisme, Moderasi, dan Progresivisme di Era Digital - Naufal, Muflih; Santalia, Indo; Rijal, Tabhan Syamsu (FASTABIQ: JURNAL STUDI ISLAM, 2025)
This article aims to analyze the dynamics of religious discourse in Indonesia during the COVID-19 crisis, focusing on how ideological contestations reflect shifting meanings and religious authority within the digital public sphere. The study employs a qualitative approach using library research and Foucauldian critical discourse analysis, combined with content and comparative analysis of responses from major Islamic institutions such as the MUI, Nahdlatul Ulama, and Muhammadiyah. The theoretical framework draws on Michel Foucault's concept of discourse and power, along with John Storey's theory of cultural ideology. The findings reveal that the pandemic triggered three ideological spectrums of religious response—conservative, moderate, and progressive—each representing distinct theological stances toward worship, public health policy, and religious legitimacy. Social media emerged as a new arena of authority, where digital religious narratives often surpassed institutional fatwas in influence. The study concludes that the pandemic acted as a catalyst for the transformation of religious discourse, with long-term implications for the relationship between religion, state, and civil society in the digital era. It recommends more participatory, adaptive, and collaborative religious communication strategies to strengthen social cohesion and religious moderation in post-crisis contexts.Keywords: social crisis; religious discourse; religious ideology; digital authority; Foucault, pandemic